Readings in African traditional religion: structure, meaning, relevance, future - Uka, Emele M. (Peter Lang, 1991)
This book consists of classic articles on African Traditional Religion by eminent scholars in the field. It has six sections. The first one deals with definitions and how the African perceives his world; the second looks at ATR in terms of its academic, historical, western and methodological perspectives. The third examines some vital elements of the theology, spirituality, ethics and salvific value of ATR. Section four reviews the impact of ATR in its environment as it bears on family life, nation building, education and health. Section five examines the encounter of ATR with world missionary religions like Christianity and Islam. The final section, which ends with a selected bibliography on the subject considers the future and the way forward for ATR. The book is designed as a resource and reference material for anyone interested in the field of Religion. It will also appeal to both scholars and students in the field of Religious studies, Sociology of Religion, Comparative study of Religions and «Mission» studies.
Keywords: Christianity and African religions; Christians – Africa